2007
DOI: 10.1111/j.1524-4741.2007.00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Trial of a Computerized Decision Aid for Breast Cancer Prevention

Abstract: This study sought to evaluate a shared decision-making aid for breast cancer prevention care designed to help women make appropriate prevention decisions by presenting information about risk in context. The decision aid was implemented in a high-risk breast cancer prevention program and pilot-tested in a randomized clinical trial comparing standard consultations to use of the decision aid. Physicians completed training with the decision aid prior to enrollment. Thirty participants enrolled (15 per group) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…This integration may be reason other, well developed tools [18], have not been widely adopted in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…This integration may be reason other, well developed tools [18], have not been widely adopted in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…First, the educators who were responsible for provision of patient education in both groups were not blinded to the experimental intervention and may have been more motivated to support control participants in making decisions. This may have diminished the impact of our DA on decisional conflict as well as reduced the probability to detect between-group differences, as reported elsewhere [6870]. Second, to measure asthma control, we could have used either the Asthma Control Questionnaire [71, 72] or the Asthma Control Test [73, 74], for which the minimally important differences had already been estimated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was reported that Internet is a more effective method than written educational materials to increase knowledge (Street et al, 1995). Ozanne et al (2007) carried out a study about computerized decision aid for breast cancer prevention. Their findings showed that the level of patients' information competence that spent more time in using Internet was higher than patients who spent less time using this kind of services.…”
Section: Role Of Internet On Breast Cancer Patientsmentioning
confidence: 99%